Dampak Kesehatan Mental Pada Tenaga Kesehatan Dan Pasien di ICU Dengan Covid-19: A Literature Review - Nor Rahayu; Nurlaila Fitriani; Supratman Supratman (FORIKES, 2022)
The increase in Covid-19 has had a considerable impact in the health service sector, including in the Intensive Care Unit. The impact felt by health workers and patients in the Intensive Care Unit, is not only in terms of physical, but also psychological. Psychological responses are felt differently. The purpose of this literature review is to identify more deeply, the impact of mental health on health workers and patients with Covid-19 in the ICU. Search articles using three databases, namely PubMed, Sciencedirect, Willey Online Library. Based on the search results, 324 articles were found, and 9 of them according to the inclusion and exclusion criteria were used. It was concluded that Covid-19 had a negative impact on the mental health of health workers and patients with Covid-19 in the Intensive Care Unit.Keywords: Covid-19; mental health; health workers; patient; Intensive Care UnitABSTRAK Peningkatan Covid-19 memberi dampak cukup besar di bidang pelayanan kesehatan termasuk di Intensive Care Unit. Dampak yang dirasakan oleh tenaga kesehatan dan pasien di Intensive Care Unit, tidak hanya dari segi fisik, tetapi juga psikologis. Respon psikologis yang dirasakan berbeda-beda. Tujuan literature review ini adalah untuk mengidentifikasi secara lebih dalam, dampak kesehatan mental pada tenaga kesehatan dan pasien dengan Covid-19 di ICU. Pencarian artikel menggunakan tiga database, yaitu PubMed, Sciencedirect, Willey Online Library. Berdasarkan hasil pencarian didapatkan 324 artikel, dan 9 di antaranya sesuai dengan kriteria inklusi dan ekslusi digunakan. Disimpulkan bahwa Covid-19 berdampak buruk pada kesehatan mental tenaga kesehatan dan pasien dengan Covid-19 di Intensive Care Unit.Kata kunci: Covid-19; kesehatan mental; tenaga kesehatan; pasien; Intensif Care Unit